Pengaruh Fraud Risk, Karakteristik Auditor Independen, dan Kinerja Perusahaan Terhadap Kualitas Audit - Salsabila Syifa; Hexana Sri Lastanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of fraud risk, workload, auditor specialization, and company performance on audit quality in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The method used is a quantitative approach with secondary data obtained from company financial reports. Audit quality is measured using the absolute value of discretionary accruals based on the Modified Jones model. The results indicate that fraud risk, workload, and auditor specialization do not significantly affect audit quality, while company performance does. These findings emphasize the importance of auditors' competence and experience in specific industries, as well as company financial performance, in supporting better audit quality.